Digital Transformation of Local Political Parties: A Case Study of PDIP and PAN in East Java - Suwarko, Andi (JPP (Jurnal Politik Profetik), 2026)
Digital disruption forces political intermediaries to evolve or face obsolescence. While national-level digital transformation is well-documented, grassroots dynamics within local party branches remain under-researched, leaving a significant gap in emerging democracies. This study argues that digital transformation at the subnational party level does not inherently catalyze democratic deepening; rather, it functions as a mechanism of 'Pragmatic Digitalization' that solidifies traditional hierarchical power structures. Focusing on the East Java provincial branches of the Indonesian Democratic Party of Struggle (PDIP) and the National Mandate Party (PAN), this qualitative multi-site case study examines how local party machinery navigates this shift. Utilizing a four-dimensional framework adoption, management, deliberation, and participation, the findings demonstrate that while both parties successfully transition into 'Hybrid Parties' by professionalizing administrative governance (via SIPP and SimPAN applications), this transformation remains structurally partial. Digital tools are weaponized primarily for top-down communication and organizational survival rather than fostering horizontal intra-party democracy. Ultimately, this research refines 'Digital Party' theory by exposing a distinct Global South paradigm: digitalization professionalizes party bureaucracy to build a 'digital armor' for organizational resilience while strategically preserving localized elite hegemony.